2017
DOI: 10.1111/bjh.14829
|View full text |Cite
|
Sign up to set email alerts
|

Nilotinib dose‐optimization in newly diagnosed chronic myeloid leukaemia in chronic phase: final results from ENESTxtnd

Abstract: SummaryThe Evaluating Nilotinib Efficacy and Safety in Clinical Trials–Extending Molecular Responses (ENESTxtnd) study was conducted to evaluate the kinetics of molecular response to nilotinib in patients with newly diagnosed chronic myeloid leukaemia in chronic phase and the impact of novel dose‐optimization strategies on patient outcomes. The ENESTxtnd protocol allowed nilotinib dose escalation (from 300 to 400 mg twice daily) in the case of suboptimal response or treatment failure as well as dose re‐escalat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 20 publications
2
22
1
Order By: Relevance
“…Regarding patient background characteristics in the ENESTxtnd trial, 23 GIMEMA trial, 25 and the present N‐Road study, the median age (range) was comparable. The rates of high Sokal score were no data, 23 21%, 25 and 13%, respectively. A higher MR 4.5 accumulative rate in this study may have been a result of the inclusion of fewer individuals who had a high Sokal score within our sample.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Regarding patient background characteristics in the ENESTxtnd trial, 23 GIMEMA trial, 25 and the present N‐Road study, the median age (range) was comparable. The rates of high Sokal score were no data, 23 21%, 25 and 13%, respectively. A higher MR 4.5 accumulative rate in this study may have been a result of the inclusion of fewer individuals who had a high Sokal score within our sample.…”
Section: Discussionmentioning
confidence: 58%
“…The N‐Road study aimed to achieve early response; thus, the dose increase criteria for no optimal response at 3, 6, and 12 months recommended by ELN 2013 was applied in this study 26 . The dose increase criteria applied in N‐Road were, therefore, even stricter than those of ENESTxtnd 23 and GIMEMA trials 24,25 . Consequently, the cumulative rate of MR 4.5 by 24 months was high in our study.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…1) due to the few clinical trials in these settings. However, the efficacy of bosutinib, which shares its dual SRC/ABL-inhibitory activity with dasatinib, is markedly reduced (CCyR 17% vs. 54% and MCyR 43% vs. 78%) after imatinib and dasatinib failure compared with its use in dasatinib-naïve patients, e. g., those having failed imatinib and nilotinib [25, 26].
Fig.
…”
Section: Second- and Later-line Treatmentsmentioning
confidence: 99%
“…Typical adverse events of nilotinib include hepatic dysfunction, elevated bilirubin, prolongation of QTc interval, hyperlipidemia, and hyperglycemia. Hepatotoxicity caused by other tyrosine kinase inhibitors is known, but it is reported that the frequency of nilotinib hepatotoxicity is rare . When hepatic dysfunction occurs, drug withdrawal or dose reduction is required, but there are currently no indicators for dose adjustment.…”
Section: Introductionmentioning
confidence: 99%